Catalyst‐Free and Visible Light Promoted Aminofluoroalkylation of Unactivated Alkenes: An Access to Fluorinated Aziridines. Issue 13 (5th May 2020) - Liu, Xiao‐Xiao; Jia, Jia; Wang, Ze; Zhang, Yu‐Ting; Chen, Jiao; Yang, Ke; He, Chun‐Yang; Zhao, Liang
Abstract: Fluorinated aziridines are very important structural motifs, but methods access to such structures are still very rare. In this paper, we report a mild, catalyst‐free and operationally simple strategy for the direct aminofluoroalkylation of olefins driven by the noncovalent interaction between N ‐allylanilines and fluoroalkyl iodides. This photochemical transformation features synthetic simplicity, mild reaction conditions, without the use of any photoredox catalyst, and high functional group tolerance. Moreover, the structures can be used as important precursors for the synthesis of β ‐fluoroalkylated alkylamine derivatives, such as fluorinated amino acids and fluorinated 2‐pyrrolidinones. Abstract :